ESSENTIAL PECULIARITIES OF MEDIADISCOURSE (KONFERENSIYA, 2025)
This article deals with one of the urgent problems of modern linguistics. That isrelated to media-discourse and its types. As we know, the main type of discourse ismedia-discourse. The article focuses on essential features of media-discourse bypointing out types including press, TV, internet media. Media-discourse has becomea global space of conveying messages by distributing information to the public,besides it is the tool to persuade individuals in society by making them grasped to theintended ideology